Plasmonic photothermal catalysis for solar-to-fuel conversion: current status and prospects. Issue 16 (23rd March 2021) - Luo, Shunqin; Ren, Xiaohui; Lin, Huiwen; Song, Hui; Ye, Jinhua
Abstract : Hot carrier activation and photothermal heat can be constructively coupled using plasmonic photothermal catalysts for synergistically promoted solar-to-fuel conversion efficiency. Abstract : Solar-to-fuel conversion through photocatalytic processes is regarded as promising technology with the potential to reduce reliance on dwindling reserves of fossil fuels and to support the sustainable development of our society. However, conventional semiconductor-based photocatalytic systems suffer from unsatisfactory reaction efficiencies due to limited light harvesting abilities. Recent pioneering work from several groups, including ours, has demonstrated that visible and infrared light can be utilized by plasmonic catalysts not only to induce local heating but also to generate energetic hot carriers for initiating surface catalytic reactions and/or modulating the reaction pathways, resulting in synergistically promoted solar-to-fuel conversion efficiencies. In this perspective, we focus primarily on plasmon-mediated catalysis for thermodynamically uphill reactions converting CO2 and/or H2 O into value-added products. We first introduce two types of mechanism and their applications by which reactions on plasmonic nanostructures can be initiated: either by photo-induced hot carriers (plasmonic photocatalysis) or by light-excited phonons (photothermal catalysis). Then, we emphasize examples where the hot carriers and phonon modes act in concert to contribute to the reaction (plasmonic photothermal catalysis), with special attention given to the design concepts and reaction mechanisms of the catalysts. We discuss challenges and future opportunities relating to plasmonic photothermal processes, aiming to promote an understanding of underlying mechanisms and provide guidelines for the rational design and construction of plasmonic catalysts for highly efficient solar-to-fuel conversion.